Effectiveness of Kegel Education for The Elderly as A Form of The Authority of The Midwife in Community Midwife Care - Ni Made Karlina Sumiari Tangkas; Indrie Lutfiana; Ni Made Ayu Wulandari (Chakra Brahmanda Lentera Institute, 2022)
Background: The ageing process is usually characterized by physical, biological, mental, or psychosocial changes. Kegel exercises are beneficial for strengthening the double muscles of the pelvic floor, thereby strengthening the function of the external sphincter of the bladder. The research purposes were to prove the Effectiveness of Kegel Education for The Elderly as A Form of The Authority of The Midwife in Community Midwife Care Methods: The method used in the pra experiment in this community service activity is divided into three stages and is supported through a pretest and posttest to evaluate activities. An evaluation is carried out after one month of providing education. The population was all older adults, and This activity was attended by 27 older adults in the Tabanan I Health Center. Results: The result of the research show that the average score of the frequency of urination before being given Kegel exercises was 0.19 after being given Kegel exercises of 0.85. It also obtained an at-count value of -6.245 and a p-value of 0.000 < (0.05) so that it can be concluded that Kegel exercise education influences the elderly in the Tabanan Health Center area. Conclusion: Education Kegel exercises affect urinary incontinence. Kegel exercise can stimulate and increase the activation of chemical, neuromuscular, and muscular in the pelvic muscles so that it can reduce the frequency of urination in the elderly. Providing education related to Kegel exercise will greatly assist midwives in carrying out the midwife's authority in community care.